Phylogenetic relationships of spatangoid sea urchins (Echinoidea): taxon sampling density and congruence between morphological and molecular estimates - Stockley, B.; Smith, A. B.; Littlewood, T.; Lessios, H. A.; Mackenzie-dodds, J. A. (Zool Scripta, 2005)
A phylogeny for 21 species of spatangoid sea urchins is constructed using data from three genes and results compared with morphology-based phylogenies derived for the same taxa and for a much larger sample of 88 Recent and fossil taxa. Different data sets and methods of analysis generate different phylogenetic hypotheses, although congruence tests show that all molecular approaches produce trees that are congruent with each other. By contrast, the trees generated from morphological data differ significantly according to taxon sampling density and only those with dense sampling (after a posteriori weighting) are congruent with molecular estimates. With limited taxon sampling, secondary reversals in deep-water taxa are interpreted as plesiomorphies, pulling them to a basal position. The addition of fossil taxa with their unique character combinations reveals hidden homoplasy and generates a phylogeny that is compatible with molecular estimates. As homoplasy levels were found to be broadly similar across different anatomical structures in the echinoid test, no one suite of morphological characters can be considered to provide more reliable phylogenetic information. Some traditional groupings are supported, including the grouping of Loveniidae, Brissidae and Spatangidae within the Micrasterina, but the Asterostomatidae is shown to be polyphyletic with members scattered amongst at least five different clades. As these are mostly deep-sea taxa, this finding implies multiple independent invasions into the deep sea.
CAML